Intramuscular Ziprasidone Dosing for Acute Agitation in the Pediatric Emergency Department: An Observational Study. (February 2018) - Nguyen, Tammy; Stanton, Jillian; Foster, Robin
Background: Intramuscular (IM) ziprasidone is often used to manage acute agitation. Limited data exist on the pediatric dosing of ziprasidone in the emergency department (ED). Objective: To characterize the mg/kg dosing differences between pediatric ED patients who respond to an initial dose of ziprasidone versus patients who do not. Methods: This was a retrospective, observational study of 5- to 18-year-old patients who were treated with IM ziprasidone in the pediatric ED from 2007 to 2015. Medical records were reviewed to determine demographic and clinical information. Patients were deemed responders to ziprasidone if they required no additional rescue medication for acute agitation within 30 minutes of the initial dose. Results: Forty children received 50 doses of IM ziprasidone. Twenty-seven (68%) patients responded to the initial ziprasidone dose, requiring no further medication intervention for their acute agitation. Responders were given a mean initial dose of 0.19 ± 0.1 mg/kg, while nonresponders were given an initial mean dose of 0.13 ± 0.06 mg/kg ( P = .03). Conclusion: A significant dose difference exists between patients who required only one initial dose of ziprasidone compared to those who required additional medication. As a result, an initial dose of 0.2 mg/kg of IM ziprasidone may be considered when managing acutely agitated pediatric patients in the ED.